2022
DOI: 10.1016/j.jped.2021.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Fast, cheap and feasible: Implementation of pediatric telemedicine in a public hospital during the Covid-19 pandemic

Abstract: Objective In Brazil, telemedicine was allowed as an exception during the coronavirus disease (COVID-19) pandemic. Despite its recognized value and availability, telemedicine is not universally used, suggesting that some barriers prevent its adoption and acceptance within the community. This study aims to describe the implementation of a low-cost telemedicine service in a pediatric hospital in Brazil. Method Retrospective descriptive study reporting the first three month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
(40 reference statements)
1
7
0
1
Order By: Relevance
“…Regarding "assessment of therapeutic contact" general acceptance and high satisfaction were found with all the counseling formats also in line with similar studies that report the "evaluation of the therapeutic contact" in both telecounseling and face-to-face contact as satisfactory, trusting and appreciative (23,24). Here it should be noted that the majority of the sessions in the study, were individual sessions and did not take place in the context of therapy.…”
Section: Discussionsupporting
confidence: 88%
“…Regarding "assessment of therapeutic contact" general acceptance and high satisfaction were found with all the counseling formats also in line with similar studies that report the "evaluation of the therapeutic contact" in both telecounseling and face-to-face contact as satisfactory, trusting and appreciative (23,24). Here it should be noted that the majority of the sessions in the study, were individual sessions and did not take place in the context of therapy.…”
Section: Discussionsupporting
confidence: 88%
“…The PATMHO is pioneer in offering telemedicine in a public and exclusively pediatric tertiary service. 6 The present study demonstrates an avant-garde telemedicine training initiative for pediatric residents, focusing on pediatric emergencies. Telemedicine is probably one of the legacies of the COVID-19 pandemic 14 , 17 and we observed that the pediatric residents of our service already recognize the importance of learning more about virtual care.…”
Section: Discussionmentioning
confidence: 90%
“…Also, most consultations involved reassessments of face-to-face evaluations with similar complaints of respiratory problems during the pandemic. 6 We considered that there were few cases/residents (approximately 9 per semester) due to the service being new and still in the initial years of implementation. Even so, residents considered that there was no impairment in learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Economic impact of telehome care will also be evaluated. As reported, home hospitalization allows cost optimization, both structural and personnel expenses [ 14 17 ]; prospectively telehomecare in the pediatric field can cost up to 9% less than standard care [ 14 ].…”
mentioning
confidence: 99%